1994
DOI: 10.1016/0014-5793(94)00867-1
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent differential display: Arbitrarily primed RT‐PCR fingerprinting on an automated DNA sequencer

Abstract: We established robust, reliable protocols for 'Differential Display (DD),' an RNA fingerprinting method originally developed by Liang and Pardee [0992) Science 257, 967~71] using RT-PCR with arbitrary primers. Our protocols are optimized so that reliable DD analysis can be performed on a fluorescent DNA sequencer to ensure high throughput as well as improved operational safety, compared with the original one using radioactive compounds. Such 'Fluorescent Differential Display (FDD)' techniques will accelerate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
114
0
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 182 publications
(117 citation statements)
references
References 15 publications
2
114
0
1
Order By: Relevance
“…Fluorescent differential display (FDD) was performed according to a previously described method (14). Anthers of S 8 and S 12 homozygotes of B. campestris were collected from flower buds of 1-10 mm in length that span most developmental stages.…”
Section: Methodsmentioning
confidence: 99%
“…Fluorescent differential display (FDD) was performed according to a previously described method (14). Anthers of S 8 and S 12 homozygotes of B. campestris were collected from flower buds of 1-10 mm in length that span most developmental stages.…”
Section: Methodsmentioning
confidence: 99%
“…Di¡erential display of mRNAs by PCR [6,7] Reverse transcription (RT) was performed by incubation of 2. . The durations and temperatures used were 3 min at 94³C, 5 min at 40³C, and 1 min at 72³C for the initial cycle and 15 s at 94³C, 2 min at 40³C, and 1 min at 72³C for subsequent 25 cycles.…”
Section: Removal Of Contaminating Chromosomal Dnamentioning
confidence: 99%
“…In the present study, we adopted a rat experimental model for vasospasm 6 and used fluorescence differential display (FDD) 7 to identify differentially expressed genes and to evaluate the functional significance of such genes in vasospasm of the basilar artery. We identified that heat shock protein 72 (HSP72) was a gene highly sensitive to upregulation by cerebral vasospasm after SAH and that overexpression of HSP72 is a possible mechanism involved in the prevention and treatment of pathological conditions such as delayed cerebral vasospasm.…”
mentioning
confidence: 99%